Le corps respirant : la pensée physiologique chez Galien - Debru, Armelle. (Studies in Ancient Medicine, 1996)
This volume provides a new approach to Galen's theory of respiration and to his physiological thinking. The method involves reconstructing Galen's theoretical and experimental research in the structure and context of his reasoning. The book deals with the problem of muscular respiratory movement, the structure and function of organs such as the heart, lungs and pulmonary vessels, and the purpose of breathing. Other topics include bodily respiration (diapnoe), the explanation of asphyxia, miasmas and other pathological processes. The book ends with a study of breathing and vocal exercises in the Greco-Roman world. This is an important reassessment of several questions that are fundamental to the history of medicine; it provides a truer understanding of one of the most impressive contributions to western medical thought.